Responds of Superior Teak (Tectona grandis) on Different Sulphur Concentrations - Lestari, Puji; Arifriana, Ridla; Nurjanto, Handojo Hadi (Jurnal Sylva Lestari, 2019)
The tree improvement program has invented superior teak with an ability to improve its productivity. Yet the information about basic nutrient requirement of superior teak is less known. This study aimed to determine the optimal concentration of sulfur for the best growth of superior teak seedling and to identify the morphological symptoms of teak seedlings affected by several concentration levels of S. This study was conducted at a nursery on six months old teak seedlings. The experimental design was Completely Randomized Design (CRD) with four different solution treatments with three replication each. The treatments are K (control, aqua dest does not contain nutrients), S0 (solution contains nutrients except sulfur), S1 (solution contains nutrients with 0,5 full strength of S), and S2 (solution contains nutrients with full strength of S). Each treatment was replicated 3 times. Parameter observed included the height of seedling, the diameter of seedling, the nodal distance of seedling, the number of leaves, size of leaves and morphological symptoms of leaf. The results showed that at a concentration of nitrogen (N), phosphor (P), potassium (K), calcium (Ca), and magnesium (Mg) in full strength level, superior teak seedling which treated by S1 (S concentration of 421 ppm) resulted in the best growth. However, the morphology of teak leaves in all treatment showed abnormal.Keywords: growth, morphology, sulfur, superior teak